Winning at Collective Bargaining: Strategies Everyone Can Live With - Sharp, William L. (Rowman & Littlefield Publishers, 2003)
Whether you are a novice or a seasoned pro, the information and strategies outlined in this collective bargaining guide will enable you to come to the table and negotiate successfully. Comprehensive in scope, the text begins with an historical overview and discussion of state bargaining laws. Other chapters are devoted to describing the roles of the negotiators, the negotiation process and procedures, and creating win-win situations. Strikes and contract management are also addressed. End of chapter discussion questions along with helpful summaries and lists of resources for future reference contribute to the book's value as a text for graduate students enrolled in a course in Collective Bargaining or Personnel in Educational Administration. Practitioners, especially board members, superintendents, school attorneys, negotiators, and other school administrators will find the chapters containing practical and specific suggestions for successful negotiations to be beneficial.